'La ferme vérité de sa forte agonie': The Suffering Christ in the Poetry of Jean de La Ceppède. Issue 2 (3rd July 2017) - Parish, Richard
Abstract : One of the outstanding poetic achievements of the French Counter-Reformation is the sonnet sequence of Jean de La Ceppède (1550-1623), the full title of which is Les Théorèmes sur le sacré mystère de notre Rédemption, and which appeared in a form whose combination of intense formal focus and broad narrative development is particularly appropriate to the subject. The collection, published in two stages (dating from 1613 and 1622) is at once erudite, physical, penitential and precise, under which broad headings it is discussed in the first part of this article, which concentrates on the detailed attention accorded to the specifics of Christ's suffering body before and during the Crucifixion, often in a strikingly painterly fashion. Two other features stand out: first, the existence of frequently very extensive Annotations, in which the whole panoply of patristic and later erudition is applied to features of the episodes depicted; and, then, the potential for their evocation to serve as meditational and penitential stimuli for the poet persona and, through him, for the reader. The second part of the article turns to the status of the wounds of Christ in the post-Resurrection appearances, as a means of restoring to the risen body some of the previous physical beauty implicitly evoked in the earlier pieces.